Civil society in investment treaty arbitration : status and prospects - El-Hosseny, Farouk (Nijhoff international investment law series, 2018)
"Civil Society in Investment Treaty Arbitration: Status and Prospects provides an overview of the evolution of civil society's participation as amicus curiae before ICSID tribunals and ad hoc tribunals applying the UNCITRAL Arbitration Rules. That evolution fits within a broader movement towards transparency in investment treaty arbitration. By look at the procedural roles available to civil society before other jurisdictions, the book questions whether the amicus role could be expanded. El-Hosseny ultimately shows how substance and procedure closely intertwine. The issue of civil society's participation in investment treaty arbitration transcends the procedural realm. It is equally about arbitral tribunals' openness vis-à-vis public interest, environmental protection and human rights issues--a crucial consideration in ongoing debates over the legitimacy, and future, of investor-state arbitration."